EFFECTIVENESS OF OZONE THERAPY IN REHABILITATION OF NEWBORNS AFTER INTRAUTERINE HYPOXIA - Z. I. MIKASHINOVICH; I. A. LOGINOV; A. A. BORSHCHEVA (Кубанский научный медицинский вестник, 2017)
Aim. To estimate efficiency of inhalation ozone therapy at rehabilitation of newborns who had suffered from intrauterine hypoxia.Materials and methods. The complex clinical laboratory research of the antioxidant status of 150 newborns was conducted. The control group included 30 almost healthy newborns whose mothers had no somatic diseases and were characterized by physiological gestation course. The group of comparison was presented by 45 newborns whose mothers had secondary chronic placental insufficiency and received drug treatment without the course of ozone therapy. 75 newborns whose mothers received ozone-air mixture inhalations along with traditional therapy entered into clinical group. The erythrocytes of newborns’ dark blood taken right after the birth were chosen as a material for the research. The activity of superoxide dismutases (SOD), catalases, glutathione peroxidases (GPO), glutathione reductase (GSR), glucose-6-phosphate dehydrogenase (G6PD), as well as concentration of the restored glutathione (GSH) were assayed. Results. It was established that the compensatory and adaptive reactions providing elimination of the reasons of oxidizing stress development due to the stimulating influence of ozone on activity of antioxidant protection enzymes were formed in newborns of clinical group.Conclusion. In this regard, the offered scheme of the ozone therapy can be recommended for a complex rehabilitation of pregnant women with the chronic secondary placental insufficiency against the background of cardiovascular diseases.